Diseases of swans in captivity - Brown, Martin J; Linton, Emma; Rees, Eileen C (Wildfowl, 1992)
The results of post mortem data from 373 swans that died within Wildfowl and Wetlands Trust collections between 1951 and 1989 inclusive were analyzed. The most common causes of death were tuberculosis and visceral gout in adult swans, acuaria in juveniles, and pneumonia, omphalitis and trauma in downies. Differences between the species in their levels of susceptibility to the different diseases are described and further improvements in husbandry technique are propounded.